Blepharospasm with elevated anti-acetylcholine receptor antibody titer - Tang, Min; Li, Wu; Liu, Ping; He, Fangping; Ji, Fang; Meng, Fanxia (Arquivos de Neuro-Psiquiatria, 2018)
Objective: To determine whether serum levels of anti-acetylcholine receptor antibody (anti-AChR-Abs) are related to clinical parameters of blepharospasm (BSP).Methods: Eighty-three adults with BSP, 60 outpatients with hemifacial spasm (HFS) and 58 controls were recruited. Personal history, demographic factors, response to botulinum toxin type A (BoNT-A) and other neurological conditions were recorded. Anti-AChR-Abs levels were quantified using an enzyme-linked immunosorbent assay.Results: The anti-AChR Abs levels were 0.237 ± 0.022 optical density units in the BSP group, which was significantly different from the HFS group (0.160 ± 0.064) and control group (0.126 ± 0.038). The anti-AChR Abs level was correlated with age and the duration of response to the BoNT-A injection.Conclusion: Patients with BSP had an elevated anti-AChR Abs titer, which suggests that dysimmunity plays a role in the onset of BSP. An increased anti-AChR Abs titer may be a predictor for poor response to BoNT-A in BSP.
Keywords: Blepharospasm; hemifacial spasm; botulinum toxin type A